The role of C and Mn at the austenite/pearlite reaction front during non-steady-state pearlite growth in a Fe–C–Mn steel. (15th July 2015) - Aranda, M.M.; Rementeria, R.; Poplawsky, J.; Urones-Garrote, E.; Capdevila, C.
Abstract : The role of C and Mn during the growth of pearlite under non-steady state conditions is analyzed by comparing phase compositions of austenite, ferrite and cementite (γ+α+θ) through the use of transmission electron microscopy (TEM), energy dispersive X-ray spectroscopy (EDS), and atom probe tomography (APT) measurements across the austenite/pearlite interface. A local Mn enrichment and C depletion at the austenite/pearlite interface has been measured, which causes a change in the transformation driving force with time during divergent pearlite growth.